PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2024 - Melysa Yeremia Arta Ulina Silaen; Jeudi A.T.P. Sianturi; Merry Anna Napitupulu (STKIP Subang, 2026)
The energy sector is a capital-intensive industry with a high level of risk influenced by economic dynamics and fluctuations in commodity prices. These conditions require companies to maintain strong financial performance in order to sustain firm value in the eyes of investors. This study aims to analyze the effect of firm size, capital structure, and profitability on firm value through dividend policy as a mediating variable in energy sector companies listed on the Indonesia Stock Exchange during the period 2021–2024. This research employs a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample was determined through a purposive sampling method using secondary data obtained from companies’ annual financial statements. Firm size is proxied by the natural logarithm of total assets, capital structure by the Debt to Equity Ratio (DER), profitability by Return on Assets (ROA), dividend policy by the Dividend Payout Ratio (DPR), and firm value by Tobin’s Q. The results show that firm size and capital structure have a negative and significant effect on firm value, while profitability has a negative but insignificant effect on firm value. Firm size and profitability have a negative and significant effect on dividend policy, whereas capital structure does not have a significant effect on dividend policy. In addition, dividend policy does not have a significant effect on firm value and is not proven to mediate the relationship between firm size, capital structure, and profitability on firm value. These findings indicate that firm size and capital structure play an important role in influencing firm value directly, while dividend policy does not act as an effective mechanism in mediating the relationship between fundamental corporate variables and firm value in energy sector companies.